2019
DOI: 10.1093/nar/gkz689
|View full text |Cite
|
Sign up to set email alerts
|

AT-dinucleotide rich sequences drive fragile site formation

Abstract: Common fragile sites (CFSs) are genomic regions prone to breakage under replication stress conditions recurrently rearranged in cancer. Many CFSs are enriched with AT-dinucleotide rich sequences (AT-DRSs) which have the potential to form stable secondary structures upon unwinding the double helix during DNA replication. These stable structures can potentially perturb DNA replication progression, leading to genomic instability. Using site-specific targeting system, we show that targeted integration of a 3.4 kb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Poly dA:dT tracks have been involved in the instability of early-replicating fragile sites (ERFS), another type of instable sequences associated with short, highly transcribed and early-replicating genes 42,43 . In addition, a recent report has shown that a 3.4 kb dA:dT dinucleotide sequence targeted to the 40 kb long early-replicating HGPRT gene triggers instability of this house-keeping gene 44 . Therefore, sequences able to form secondary structures may become instable in some chromosome contexts, notably ERFS, but not in the context of modestly transcribed large late-replicating genes.…”
Section: Discussionmentioning
confidence: 99%
“…Poly dA:dT tracks have been involved in the instability of early-replicating fragile sites (ERFS), another type of instable sequences associated with short, highly transcribed and early-replicating genes 42,43 . In addition, a recent report has shown that a 3.4 kb dA:dT dinucleotide sequence targeted to the 40 kb long early-replicating HGPRT gene triggers instability of this house-keeping gene 44 . Therefore, sequences able to form secondary structures may become instable in some chromosome contexts, notably ERFS, but not in the context of modestly transcribed large late-replicating genes.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another possibility is that the DNA sequences present within the CFSs may be inherently difficult to replicate due to their propensity to adopt atypical secondary structures. 16,[32][33][34][35][36] Interestingly, treatment of cells with aphidicolin leads not only to breaks and gaps on mitotic chromosomes, but also to foci of nascent DNA synthesis that decorate these chromosomes. 37 These foci represent sites of so-called mitotic DNA synthesis (MiDAS), and generally colocalize with FANCD2 foci and with ultrafine anaphase bridges, which mark the chromosomal positions of CFSs in cells exposed to aphidicolin.…”
Section: Introductionmentioning
confidence: 99%
“…4 d). Though the biological significances of the other 102 peaks are not reported as many SSRs being lacking of understanding in human Y-DNA originally, these peaks may also play some important biological roles potentially, which probably deserve to be further explored [ 6 , 10 , 42 45 ]. In addition, those middle and low peaks possibly be also helpful to some biological process.…”
Section: Discussionmentioning
confidence: 99%